Donner naissance: doulas, sages-femmes & justice reproductive - Apfel, Alana; Ross, Loretta J.; Law, Victoria; Federici, Silvia; Pruvost, Geneviève; Tincelin, Adel (Cambourakis, 2024)
Donner naissance . Doulas, sages-femmes & justice reproductive . Alana Apfel nous propose un recueil vivant de treize récits écrits par des doutas, des sages-femmes et des activistes féministes aux États-Unis qui racontent la naissance autrement. Au modèle de la toute-puissance médicale qui saurait mieux que les femmes elles-mêmes ce qu'est un « bon » accouchement est opposé ici un tout autre professionnalisme, à la fois discret et attentif, qui permet de faire une juste place à des femmes indignement traitées. Militer pour la « justice reproductive », c'est créer des « communs » de la naissance, selon la formule de Silvia Federici dans son introduction.. La postface de Geneviève Pruvost nous rappelle que l'obstétrique française est la plus médicalisée d'Europe. À l'heure où, en France, les sages-femmes à domicile font l'objet d'une tentative d'éradication professionnelle, Donner naissance nous propose une nouvelle manière de penser les trajectoires reproductives et nous fournit les outils théoriques et pratiques nécessaires
Section: 1 vol. (262 p.) : ill. ; 18 cm.
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; care; corps; cours; discipline; justice reproductive; justice sociale; maternité; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc3113; sociologie; systèmes d'oppressions; thématiques; états-unis

La peur au ventre (Babel films, 2024)
En procédant à l’invalidation de l’arrêt Roe v. Wade, qui légalisait l’avortement aux États-Unis depuis 1973, la Cour suprême a fait un saut en arrière. Ce recul est symptomatique d’une polarisation déroutante. Dérangée par cette situation, la réalisatrice et féministe Léa Clermont-Dion s’interroge : comment ce précédent juridique aura de l’impact chez nous, au Canada ? Elle offre une exploration de la montée des groupes antiavortement au Québec, et partout au pays, mais présente aussi une plongée rare dans la riposte féministe et pro-choix qui s’organise. Après son film coup de poing Je vous salue salope : la misogynie au temps du numérique (2022), la cinéaste poursuit sa quête de justice et de vérité.
Place: Montréal
Keywords: approches et analyses; avortement; canada; discipline; discours dominant; droits des femmes*; histoire; histoire des femmes*; justice reproductive; justice sociale; militance; pro-choix; régions géographiques; santé; santé des femmes*; sciences humaines; sociologie; systèmes d'oppressions; thématiques; états-unis

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; thématiques

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Médecine et sexualité, aperçus sur une rencontre historiographique (Recherches francophones, époques moderne et contemporaine) - Chaperon, Sylvie; Hanafi, Nahema (Clio. Femmes, Genre, Histoire, 2013)
Cet article rappelle dans quelles circonstances une histoire de la sexualité construite à partir de sources médicales a émergé en France dans les années 1970. Il insiste surtout sur les pionnier-e-s de cette histoire pour les périodes moderne et contemporaine et les sources qu’ils et elles ont utilisées. Enfin il met en avant le renouvellement récent de ce champ grâce à une histoire « par en bas ».
ISBN: 9782701177816 Number: 37 Publisher: Éditions Belin
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; corps; cours; discipline; discours dominant; europe; france; histoire et politique; justice sociale; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; violences

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

Les femmes dans le champ de la santé : de l’oubli à la particularisation - Membrado, Monique (Nouvelles Questions Féministes, 2006)
L’objectif de cet article est de montrer que la réduction de la santé des femmes à leurs capacités procréatrices structure les représentations médicales à leur égard mais aussi leurs expériences de santé, et qu’elle constitue une véritable impasse pour la construction d’un cadre d’intelligibilité qui prenne en compte l’ensemble de leurs expériences. Je l’illustre à travers les catégories médicales et sociales de l’alcoolisme féminin et le rapport des femmes au cancer du sein. Enfin, je propose des pistes autour de l’intérêt porté aux trajectoires des femmes de manière à rendre visibles dans le champ de la santé les effets structurels de leur place dans la division sexuée du travail et des activités sociales.
Number: 2 Place: Lausanne Publisher: Éditions Antipodes
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; discours dominant; europe; france; justice reproductive; justice sociale; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail

Lessons from the damned: queers, whores, and junkies respond to AIDS - Stoller, Nancy E. (Routledge, 1998)
"Lessons from the Damned challenges the notion that public health theories and official organizations have the greatest impact on the fight against AIDS. Instead, Stoller looks closely at the ways the most disenfranchised - the poor, people of color, drug users, gay men and lesbians, and women - have built social movements to fight the epidemic. Drawing upon extensive ethnographic research and the words of the activists themselves, as well as the literature of social movements and theories of bureaucracy, Stoller offers guidelines for dealing with diversity and conflict and also with both theoretical and practical perspectives on cross-community and international organizing."–BOOK JACKET.
Section: xvi, 175 pages : illustrations ; 24 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; capitalisme; care; cours; discipline; histoire et politique; hétérosexisme; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; sida; soc2014; sociologie; sofia; systèmes d'oppressions; thématiques; états-unis